Respuesta :

Answer:

[tex]x=\frac{-1}{4} +/-\frac{1}{4}\sqrt{17}[/tex]

Step-by-step explanation:

First, we need to get the equation into the polynomial form. Add 8 to both sides:

[tex]-6x^{2} -2-3x=-8[/tex]

[tex]-6x^{2} +6-3x=0[/tex]

Rearrange the equation so that it is in standard form:

[tex]-6x^{2} -3x+6=0[/tex]

Remember the quadratic formula:

[tex]\frac{-b+/-\sqrt{b^{2}-4ac} }{2a}[/tex]

[tex]a[/tex], [tex]b[/tex], and [tex]c[/tex] are the coefficients of the problem when it is in standard form. In this case, [tex]a=-6[/tex], [tex]b=-3[/tex], and [tex]c=6[/tex]. Now, all we need to do is plug those into the quadratic formula.

[tex]\frac{-(-3)+/-\sqrt{(-3)^{2}-4(-6)(6)} }{2(-6)}[/tex]

Simplify:

[tex]\frac{3+/-\sqrt{153}}{-12}[/tex]

[tex]x=\frac{-1}{4} +/-\frac{1}{4}\sqrt{17}[/tex]

Hope this helps!

ACCESS MORE
EDU ACCESS
Universidad de Mexico